A SHARIA ENTREPRENEURSHIP MODEL FOR STRENGTHENING ECONOMIC INDEPENDENCE IN VOCATIONAL TAHFIDZ INSTITUTIONS: A CASE STUDY OF MA’HAD TAHFIDZ AMAN BESTARI SELANGOR - Winda Rizki Juliyanti; Muhammad Nurul Fahmi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyse and formulate a Sharia-based entrepreneurship model as a strategy to strengthen the economic independence of a vocational tahfidz institution, using Ma’had Tahfidz Aman Bestari Selangor as an in-depth case study. The scope of the research focuses on institutional business practices, governance mechanisms, and value integration within a Sharia social enterprise framework. A qualitative approach with a revelatory single case study design was employed. Data were collected through semi-structured interviews with institutional leaders and business managers, participatory observation of entrepreneurial activities, and analysis of financial and program documents. The findings reveal that Sharia entrepreneurship at the institution is implemented as an integral part of organisational governance, supported by diversified halal business units and a transparent social enterprise model. The entrepreneurship model is structured around four interrelated dimensions: maqashid-based values, institutional governance, productive economic activities, and vocational engagement. These dimensions operate in a dynamic and mutually reinforcing manner, enabling the institution to reduce dependence on external donations and enhance financial resilience. The study concludes that Sharia entrepreneurship, when institutionalised and value-driven, serves as an effective business strategy for achieving sustainable economic independence in faith-based organisations. The proposed model contributes to the literature on institutional Islamic entrepreneurship and offers a replicable framework for similar organisations seeking sustainable business development without compromising Sharia principles